Design and Implementation of a Contactless Smart House Network System - Mohammed Issam Younis; Taif Fadhil Hussein (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The Internet of Things (IoT) technology is every object around us and it is used to connect these objects to the Internet to verify Machine to Machine (M2M) communication. The smart house system is the most important application of IoT technology; it is increase the quality of life and decrease the efforts. There were many problems that faced the existing smart house networking systems, including the high cost of implementation and upgrading, high power consumption, and supported limited features. Therefore, this paper presents the design and implementation of smart house network system (SHNS) using Raspberry Pi and Arduino platforms as network infrastructure with ZigBee technology as wireless communication. SHNS consists of two main parts: the main station part and the wireless house nodes part. The local wireless communication between the house nodes and the main station is done through ZigBee technology with low power and low data rate. The mode of operation of these house nodes can be configured dynamically by the end user and determined multicast or broadcast operation according to the user requirements. The implementation and upgrading of SHNS are costless, flexible and required less power comparing with other reviewed systems.